CURRENT DEVELOPMENT OF ENTEROSCOPY - M. M. Lokhmatov (Union of pediatricians of Russia, 2014)
This review presents current data on the potential of enteroscopy - a new dynamically developing method of diagnosing jejunal diseases. Currently, two complementary methods of enteroscopy are being used - video capsule endoscopy and balloon enteroscopy. The article presents a discussion of optical systems for enteroscopy, indications for and advantages and disadvantages of methods of enteroscopy. Video capsule endoscopy is intended for initial visual assessment of jejunal mucosal condition. Depending on the position of the viewing system within the capsule, specialists distinguish between frontal and lateral systems. Balloon enteroscopy complements trials in terms of microsurgical aspects (biopsy sampling, elimination of polyps, extraction of foreign bodies, including the video capsule if it gets trapped in the stenotic portion of the intestinal lumen).